Pengukuran Kinerja Keuangan Berbasis EVA pada PT Wijaya Karya Tbk di BEI - Syahilfa , Nurul Tri; Syahira, Nazwa; Khadijah (JURNAL RISET AKUNTANSI JAMBI, 2025)
This research is to evaluate the financial performance of PT. Wijaya Karya, listed on the IDX, utilising the Economic Value Added approach.  EVA is a methodology that incorporates capital in the calculation of net operating profit after tax (NOPAT) less the capital charge.  This study employs secondary data from 2019 to 2023, which is analysed using quantitative descriptive methods.  The EVA approach is frequently employed because to its objectivity compared to financial ratio analysis, as it accounts for the cost of capital as remuneration for the utilised money.  This study used a secondary data methodology derived from the report of PT. Wijaya.  The analysed components are Net Operating Profit After Tax (NOPAT), Weighted Average Cost of Capital (WACC), and invested capital.  The study's results indicate that the EVA of PT. Wijaya Karya varied during the time.  In 2019, EVA was positive, indicating strong financial performance and enhanced value for shareholders.  Between 2020 and 2022, EVA was negative, signifying that the firm failed to make sufficient profit to offset the cost of capital, hence showing a decline in economic value.  In 2023, there is a rebound as EVA returns to a substantial positive value, but with a considerable rise in capital costs resulting from the increase in WACC.